Vocational learning for workers with intellectual disability : interventions at two case study sites - Cavanagh, Jilian [Verfasser]; Meacham, Hannah [Verfasser]; Pariona-Cabrera, Patricia [Verfasser] (My University, 2019)
"In this study, we argue that effective workplace education and training is critical to support workers with intellectual disability (WWID) at work. Moreover, we contend that it is workplace learning that prepares WWID for future career development and opportunities to enrol in and gain vocational education and training (VET) qualifications. However, management often fails to meet the needs of these workers. Our qualitative study is set in two Australian organisations where we carried out semi-structured interviews with 10 management staff and 20 WWID to examine workplace education and training for WWID. We adopted the DOTS model (decision learning; opportunity awareness; transition learning; self awareness), as the framework to unpack workplace interventions designed for WWID. The research found that opportunities to participate in workplace interventions are driven by management and WWID can be productive and successful staff members. WWID can reach levels of confidence where they seek work opportunities for development and VET qualifications. We challenge organisations to be innovative and creative, through the work-life journey of WWID, and encourage them to reach their full potential. Through effective workplace interventions more organisations can contribute to bridging the gap that often marginalises WWID" (Author's abstract; BIBB-Doku)
Keywords: G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; P 1.6 Behinderte; I 2.3.5 Australien, Ozeanien; Berufsausbildung; Berufsverlauf; Lernen am Arbeitsplatz; Lerntheorie; Menschen mit Behinderung; Fallstudie; Australien